ETHNOSCIENCE STUDY OF BEDDHA' TEMMO TYPICAL OF SUMENEP AS A NATURAL SCIENCE LEARNING RESOURCE - Firda Firda; Jefri Nur Hidayat (Jurnal Pembelajaran Sains, 2023)
This research aims to reconstruct the original science of the Kepanjin community in Sumenep City regarding the process of making beddha'temmo into scientific science, as well as explaining science material related to the reconstruction of original science in the process of making beddha'temmo. This research uses qualitative research with an ethnoscience approach. Data was collected through observation, interviews, documentation, and literature study. The research data obtained was then analyzed in several stages: reducing the data, presenting the data, and drawing conclusions/verification. Based on the results of scientific studies, the integration of beddha' temmo as one of Sumenep's local wisdom is related to junior high school science learning materials so that it can be used as a learning resource for students.